Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/gastro/goz050
|View full text |Cite
|
Sign up to set email alerts
|

Lnc-TCL6 is a potential biomarker for early diagnosis and grade in liver-cirrhosis patients

Abstract: Background Long non-coding RNAs (lncRNAs) have been applied as biomarkers in many diseases. However, scarce biomarkers are available in single lncRNA differential expression associated with different clinical stages of liver cirrhosis (LC). The aim of the study is to identify some lncRNAs that can serve as non-invasive sensitive biomarkers for early diagnosis and grade of LC. Methods Blood lncRNA expression was evaluated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…TCL6 was initially flagged as a candidate gene with potential involvement in leukemia ( 9 ). Studies have illustrated the participation of TCL6 in clear-cell renal cell carcinoma, breast cancer, retinoblastoma, liver cirrhosis and threatened abortion ( 10 , 13 , 14 , 29 , 30 ). The present results suggested that high expression of lncRNA TCL6 was associated with the pathogenesis, severity and poor prognosis of cases of preeclampsia and it may be worthwhile to explore the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…TCL6 was initially flagged as a candidate gene with potential involvement in leukemia ( 9 ). Studies have illustrated the participation of TCL6 in clear-cell renal cell carcinoma, breast cancer, retinoblastoma, liver cirrhosis and threatened abortion ( 10 , 13 , 14 , 29 , 30 ). The present results suggested that high expression of lncRNA TCL6 was associated with the pathogenesis, severity and poor prognosis of cases of preeclampsia and it may be worthwhile to explore the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with that in healthy controls, HBV carriers, and CHB patients, the expression of lnc-TCL6 was obviously upregulated in Child–Pugh A patients with liver cirrhosis. Thus, lnc-TCL6 was identified as a sensitive biomarker for early diagnosis of liver cirrhosis (Child–Pugh A)[ 29 ].…”
Section: Lncrnas In Hbv-related Chronic Diseasesmentioning
confidence: 99%
“… 1 The three main stages in the progression of HBV infection are hepatocellular carcinoma (HCC), liver fibrosis/liver cirrhosis (LF/LC) and chronic hepatitis B (CHB), or widely recognized as “hepatitis trilogy”. 2 CHB is commonly known for the heterogeneous patient features and long course of disease progression, 3 while LF is a wound healing process. Both are necessary stages for the progression from chronic liver disease to cirrhosis, and even HCC.…”
Section: Introductionmentioning
confidence: 99%